PENGARUH PEMBELAJARAN POWER LENGAN TERHADAP HASIL KEMAMPUAN TOLAK PELURU GAYA MENYAMPING - Riyanti, Yanti; Nur, Hana Astria (STKIP Muhammadiyah Kuningan, 2023)
Yanti Riyanti ( NIM 182223119 ), Health and Recreation Physical Education Study Program, 2022, page. The purpose of this study is to determine whether there is an effect of arm power learning on the results of sideways style shot put ability. This study used experimental research methods, with a pre-experimental research design. The samples used in this study were students of class 9b SMP NEGERI 2 JALAKSANA, totaling 32 people. In this study using the instrument using the Medicine Ball. The final product of the medicine ball practice is that students can throw a maximum shot put. The results of this study are data about pretest and posttest scores using the SPSS 25 program with a significant level of 0.05. The results of this study indicate that the average value of the pretest is 3.0750 and the posttest is 3.2455. With the value of the results of the t-test is 0.000 which means > 0.05, which means that there is a significant effect of the given exercise program. From the research that has been done, it can be concluded that the training model using medicine ball can be developed and applied in the sideways style shot put learning process. Keywords: learning, arm power, shot put